Conditions for Innovativeness of Industrial Entrepreneurs in Poland - Sachpazidu-Wójcicka, Karina (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2014)
Strong competition among entrepreneurs forces them to use innovation as the main source of competitive superiority. Dominating role of innovation – the factor of development - forces individual firms to search for the capability of widest use of innovation in their activity. Innovation is a result of specific process, which links up operations like presenting an idea of innovation and implementation of new solution. Proficient management of implementing the innovation process becomes important in creating innovativeness of the company. In order to be able to compete, firms must introduce new technologies, products, services and organizational systems. Nowadays innovation activity driving at bringing new products, processes, new organizational and marketing methods out is one of the most important conditions of firm market success. The paper discusses the concepts of innovativeness and analyses the theoretical conditions for its development, as well as the existing conditions for innovativeness of industrial enterprises in contemporary Poland. The objective of this paper is an analysis of statistical data (GUS) related to technology transfer of industrial entrepreneurs and its influence on innovativeness of firm. This analysis examines the efficiency of innovation activity in Polish industrial companies.